Configurations and outcomes of acute hospital care for frail and older patients with moderate to major trauma: a systematic review - Phil Moss; Heather Jarman; Mary Halter; Mark Baxter; Stefan Tino Kulnik; Lucia Gavalova; Robert Crouch; Elaine Cole; Desislava Baramova (BMJ Open)
Objective To systematically review research on acute hospital care for frail or older adults experiencing moderate to major trauma.Setting Electronic databases (Medline, Embase, ASSIA, CINAHL Plus, SCOPUS, PsycINFO, EconLit, The Cochrane Library) were searched using index and key words, and reference lists and related articles hand-searched.Included articles Peer-reviewed articles of any study design, published in English, 1999–2020 inclusive, referring to models of care for frail and/or older people in the acute hospital phase of care following traumatic injury defined as either moderate or major (mean or median Injury Severity Score ≥9). Excluded articles reported no empirical findings, were abstracts or literature reviews, or referred to frailty screening alone.Methods Screening abstracts and full text, and completing data extractions and quality assessments using QualSyst was a blinded parallel process. A narrative synthesis, grouped by intervention type, was undertaken.Outcome measures Any outcomes reported for patients, staff or care system.Results 17 603 references were identified and 518 read in full; 22 were included—frailty and major trauma (n=0), frailty and moderate trauma (n=1), older people and major trauma (n=8), moderate or major trauma (n=7) 0r moderate trauma (n=6) . Studies were observational, heterogeneous in intervention and with variable methodological quality.Specific attention given to the care of older and/or frail people with moderate to major trauma in the North American context resulted in improvements to in-hospital processes and clinical outcomes, but highlights a relative paucity of evidence, particularly in relation to the first 48 hours post-injury.Conclusions This systematic review supports the need for, and further research into an intervention to address the care of frail and/or older patients with major trauma, and for the careful definition of age and frailty in relation to moderate or major trauma.International Prospective Register of Systematic Reviews (PROSPERO) CRD42016032895.